Analysis Of Pain Relief In Emergency Room For Acute Pain In Hospital Unlversiti Sains Malaysia - Nik Hisamuddin , Nik Abdul Rahman (2001)
The objective of this study is to assess acute pain management in Accident & Emergency Department Hospital Universiti Sains Malaysia in term of degree of pain relief on leaving the unit.